"I'm not Just a Babysitter": Masculinity and Men's Experiences of First-Time Fatherhood. (October 2021) - Lewington, Lily; Lee, Jessica; Sebar, Bernadette
A man's transition into the role of a father is a rewarding yet challenging experience for many men. This study explores how men navigate contradictory roles of fatherhood and the impact this has on their identities. Fifteen first-time fathers were interviewed, and their responses were analysed using thematic and discourse analysis tools. Findings revealed that fathers both adhered to and challenge masculine ideals of fatherhood. Men described both traditional and non-traditional roles in their becoming a father, being a father, and navigating fatherhood and manhood. The continuation and contestation of masculine discourses in the experiences of fatherhood was found to influence their involvement with raising children and employment, as well as their relationships. Overall, these findings highlight the uncertainty that shapes modern fathers' roles and demonstrates how fathers move between both traditional and new fatherhood roles.